Reformulating Mission-Based Performance Indicators: A Policy Alternative for Performance-Based Budgeting in Religious Higher Education - Irwan (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2025)
This study analyzes the fundamental issues in the implementation of performance-based budgeting policy at the State Islamic University (UIN) Imam Bonjol Padang. Although the policy aims to increase efficiency, its application creates a misalignment between uniform government performance indicators and UIN’s unique mission as a religious educational institution. The research identifies the main root causes: (1) a lack of institutional policy to align performance indicators, (2) a one-size-fits-all policy approach, and (3) demands for bureaucratic and administrative efficiency. This paper uses a qualitative method with a descriptive analysis approach, USG analysis, and William N. Dunn's theory. The findings show that a regulative alternative is the most effective solution to address the root problems directly and quickly. As a recommendation, this article advises the Rector to issue new guidelines for implementing performance-based budgeting at UIN Imam Bonjol Padang, prioritizing the development of diverse and contextual performance indicators as a first step. This strategy directly addresses the core issue in performance-based budgeting: the misalignment of uniform indicators with the unique characteristics of each faculty and work unit.